Willingness to pay for Community Health Insurance among taxi drivers in Kampala City, Uganda: a contingent evaluation - Basaza R; Kyasiimire EP; Namyalo PK; Kawooya A; Nnamulondo P; Alier KP (Dove Medical Press, 2019)
Robert Basaza,1,2,* Elizabeth P Kyasiimire,1,2,* Prossy K Namyalo,3 Angela Kawooya,4 Proscovia Nnamulondo,5 Kon Paul Alier61College of Medicine, Health and Life Science, St. Augustine International University, Kampala, Uganda; 2School of Public Health and Management, International Health Sciences University, Kampala, Uganda; 3Department of Social Sciences, Ndejje University, Kampala, Uganda; 4School of Public Health and Management, Clarke International University, Kampala, Uganda; 5College of Social Sciences, Makerere University, Kampala, Uganda; 6South Sudan Institute of Pharmacy Technicians, Juba, South Sudan*These authors contributed equally to this workBackground: Community Health Insurance (CHI) schemes have improved the utilization of health services by reducing out-of-pocket payments (OOP). This study assessed income quintiles for taxi drivers and the minimum amount of premium a driver would be willing to pay for a CHI scheme in Kampala City, Uganda.Methods: A cross-sectional study design using contingent evaluation was employed to gather primary data on willingness to pay (WTP). The respondents were 312 randomly and 9 purposively selected key informants. Qualitative data were analyzed using conceptual content analysis while quantitative data were analyzed using MS Excel 2016 to generate the relationship of socio-demographic variables and WTP.Results: Close to a half (47.9%) of the respondents earn above UGX 500,000 per month (fifth quintile), followed by 24.5% earning a monthly average of UGX 300,001–500,000 and the rest (27.5%) earn less. Households in the fourth and fifth quintiles (38.4% and 20%, respectively) are more willing to join and pay for CHI. A majority of the respondents (29.9%) are willing to pay UGX, 6,001–10,000 while 22.3% are willing to pay between UGX 11,001 and UGX 20,000 and 23.2% reported willing to pay between UGX 20,001 and UGX 50,000 per person per month. Only 18.8% of the respondents recorded WTP at least UGX 5,000 and 5.8% reported being able to pay above UGX 50,000 per month (1 USD=UGX 3,500). Reasons expressed for WTP included perceived benefits such as development of health care infrastructure, risk protection, and reduced household expenditures. Reasons for not willing to pay included corruption, mistrust, inadequate information about the scheme, and low involvement of the members.Conclusion: There is a possibility of embracing the scheme by the taxi drivers and the rest of the informal sector of Uganda if the health sector creates adequate awareness.Keywords: Community Health Insurance, informal sector, willingness to pay, contingent valuation, Uganda